PENGARUH PENGAJARAN BILINGUAL DALAM PEMBELAJARAN PENJUMLAHAN PADA SISWA KELAS 4 SD NEGERI 24 KOTA SORONG : THE EFFECT OF BILINGUAL TEACHING ON ADDITIONAL MATERIAL ON GRADE 4 STUDENTS OF STATE ELEMENTARY SCHOOL 24 SORONG CITY - Hidayani; Said, Erpin; Rahayu, Eka; Awairaro, Marice; Djoroho, Theresia (Universitas Muhammadiyah Sorong, 2025)
The purpose of this study was to determine the impact of bilingual teaching on improving mathematics learning outcomes in fourth-grade students of SD Negeri 24 Sorong City, especially on addition. The research method applied was a one-group pretest-posttest design with a quantitative approach. A total of 31 students took the pretest, were then given treatment in the form of bilingual teaching (using Indonesian and English), and finally underwent a posttest with the same questions. The analysis results showed that the average score of students' pretest was 74.84, increasing to 92.26 in the posttest. Descriptive statistical tests and Paired Sample t-Test confirmed a significant difference between the pretest and posttest results (Sig. 2-tailed = 0.003). In addition to improving students' understanding of mathematics, the bilingual method also increased their engagement in the learning process, as seen from their active participation and enthusiasm during the session. Thus, bilingual learning has proven effective in supporting mathematical understanding while developing students' English skills. Based on these findings, the study recommends the implementation of innovative learning methods, such as bilingual education, to improve students' academic scores.